No way down : life and death on K2 - Bowley, Graham (New York : Harper, 2010)
'A dramatic account of the worst disaster in the history of mountain climbing on K2, the world's second highest peak'-- Provided by publisher.
Includes index.
Keywords: Mountaineering -- Pakistan -- K2 (Mountain); Mountains -- Pakistan -- K2 (Mountain) -- Difficulty of ascent; Mountaineers -- Pakistan -- K2 (Mountain); Mountaineering accidents -- Pakistan -- K2 (Mountain); K2 (Pakistan : Mountain) -- Description and travel